2009
DOI: 10.1002/ps.1831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated glyphosate applications on soil microbial community composition and the mineralization of glyphosate

Abstract: These studies suggest that the changes in the dissipation or distribution of glyphosate following repeated applications of glyphosate may be related to shifts in the soil microbial community composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 33 publications
5
81
1
1
Order By: Relevance
“…Despite the fact that glyphosate may have a direct effect on a crop plant and the respective pathogens, repeated glyphosate use has also an impact on the microbial community composition. Repeated applications favour species belonging to the group of Proteobacteria in glyphosate-treated soils than occurring in untreated control soils (Lancaster et al, 2010); glyphosate mineralisation was reduced when glyphosate was applied several times. Gimsing et al (2004) found that glyphosate mineralisation rates are positively correlated with Pseudomonas spp.…”
Section: Soil Pathogensmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the fact that glyphosate may have a direct effect on a crop plant and the respective pathogens, repeated glyphosate use has also an impact on the microbial community composition. Repeated applications favour species belonging to the group of Proteobacteria in glyphosate-treated soils than occurring in untreated control soils (Lancaster et al, 2010); glyphosate mineralisation was reduced when glyphosate was applied several times. Gimsing et al (2004) found that glyphosate mineralisation rates are positively correlated with Pseudomonas spp.…”
Section: Soil Pathogensmentioning
confidence: 91%
“…population size. However, results of Lancaster et al (2010) indicate that a repeated application of glyphosate is associated with an increase of those soil microorganisms capable of metabolising the herbicide. Altered microbial community may repress Pseudomonas species such as the beneficial species P. fluorescens and may modulate plant-pathogen interactions as well.…”
Section: Soil Pathogensmentioning
confidence: 99%
“…No major changes in community structure, assessed by CLPP and PLFA, occurred with application of field rate concentrations of glyphosate in soils from two pine plantations in California (Ratcliff et al, 2006). Both higher abundance of PLFA biomarkers of gram-negative bacteria (Weaver et al, 2007;Lancaster et al, 2009) and fungal to bacterial biomass ratios ) have been reported in glyphosate-treated soils. In a recent study, Zabaloy et al (2009) reported minor effects of glyphosate on sole C sources utilization with BDOBS.…”
Section: Microbial Community Structurementioning
confidence: 92%
“…Moreover, no adaptation to glyphosate degradation has been observed in soils with long histories of herbicide treatment (Gimsing et al, 2004). Lancaster et al (2009) reported that the total amount of 14 CO 2 evolved from glyphosate was reduced with repeated herbicide applications compared to a single application, which proved that biodegradation was not enhanced (i.e., no evidence of accelerated degradation) and was probably the result of a co-metabolic process. It is not well-known which metabolic pathway prevails in soils (Borggaard & Gimsing, 2008) although most isolated bacteria (Liu et al, 1991;Kishore & Jacob, 1987) and fungi (Sailaja & Satyaprasad, 2006) possess the sarcosine pathway.…”
Section: Metabolic Pathways Of Glyphosatementioning
confidence: 99%
“…Other hypotheses implicate gene expression adaptation and/or selection of microorganisms in soils that repeatedly received glyphosate, resulting in a shift in microbial community composition that favors species adapted to degradation of glyphosate (Lane et al, 2012;Haney et al, 2002;Araújo et al, 2003;Lancaster et al, 2010).…”
Section: Microbial Respiration Ratementioning
confidence: 99%